2012
DOI: 10.1152/ajpendo.00517.2011
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid absorption and subsequent muscle protein accretion following graded intakes of whey protein in elderly men

Abstract: Whey protein ingestion has been shown to effectively stimulate postprandial muscle protein accretion in older adults. However, the impact of the amount of whey protein ingested on protein digestion and absorption kinetics, whole body protein balance, and postprandial muscle protein accretion remains to be established. We aimed to fill this gap by including 33 healthy, older men (73 ± 2 yr) who were randomly assigned to ingest 10, 20, or 35 g of intrinsically l-[1-13C]phenylalanine-labeled whey protein ( n = 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
228
2
13

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 284 publications
(265 citation statements)
references
References 28 publications
20
228
2
13
Order By: Relevance
“…For example, we have recently demonstrated greater increases in post-exercise MPS in the elderly following bolus ingestion of 40 g vs. 20 g of whey protein [6]; a finding in contrast to our data from young adults who show a maximal MPS response with 20 g protein and no further increase with 40 g [5]. Thus, it appears that higher doses of protein [6,12], and/or leucine [13,14] to promote a greater aminoacidemia or leucinemia [7] are required by the elderly to maximize the response of MPS to protein ingestion.…”
Section: Introductioncontrasting
confidence: 99%
See 1 more Smart Citation
“…For example, we have recently demonstrated greater increases in post-exercise MPS in the elderly following bolus ingestion of 40 g vs. 20 g of whey protein [6]; a finding in contrast to our data from young adults who show a maximal MPS response with 20 g protein and no further increase with 40 g [5]. Thus, it appears that higher doses of protein [6,12], and/or leucine [13,14] to promote a greater aminoacidemia or leucinemia [7] are required by the elderly to maximize the response of MPS to protein ingestion.…”
Section: Introductioncontrasting
confidence: 99%
“…Thus, when comparing our current findings on soy protein with our previous work examining graded doses of whey protein [6], soy appears less effective than whey protein at promoting increases in MPS in the elderly ( Figure 5). Further, our results confirm that the elderly benefit from significantly greater doses of protein after exercise [6,12] than do the young, who we have shown mount a maximal MPS response with ingestion of~20 g protein [5] or~10 g EAA [2]. We have previously reported that soy protein is less effective than whey [9] and bovine milk protein [8] at increasing rates of post-exercise muscle protein synthesis in young subjects.…”
Section: Discussionsupporting
confidence: 83%
“…Muscle tissue development after birth mainly involves the elongation and augmentation of existing muscle fibers (12). Dietary nutrient levels and intestinal absorption of nutrients directly affect muscle tissue development (13). Favorable symbiosis of beneficial intestinal microflora in the intestinal tracts determines intestinal mucosal structure, intestinal function, and intestinal absorption of nutrients (14).…”
Section: Effects Of Probiotics On Growth and Development Of Broiler Mmentioning
confidence: 99%
“…As presented in previous works from our laboratory (Pennings et al 2011a, b;Pennings et al 2012;Koopman et al 2009a), we applied specifically produced intrinsically L-[1-…”
mentioning
confidence: 99%